Desenvolvimento de uma solução oral com atividade farmacológica a partir de extrato de Aspidosperma pyrifolium Mart. - Rodrigues, Jôffyli Vandenberg Morais (2015)
Herbal medicines are alternatives to the pharmaceutical industry ahead the treatment of several diseases and herbal extracts are starting point’s assets inputs for the development of these products. The Aspidosperma pyrifolium Mart. is a characteristic plant of semi-arid and it is able to provide pharmacological activities such as analgesia and anti-inflammation due to its phytochemical composition. The objective of this study was to develop an oral solution from the nebulized extract of A. pyrifolium Mart. having anti-inflammatory and analgesic activity. Three batches of the oral solution were produced: one with only the excipients used in the formulation, and two others at concentrations of 12.5 and 25.0 mg.mL . The pre- -1 formulation studies were performed with this phytomedication the aid of thermoanalytical methods and analysis in the near infrared region. The pharmacological activity was assayed by the writhing test and peritonitis in mice. The percentage inhibition of pain and inflammation were quite significant, being better than the positive control in some tests using the higher concentration solution. The quality control of the formulations was evaluated through physical, chemical and microbiological parameters, the lot of concentration 12.5 mg.mL was following all the parameters. The herbal solution developed submitted good -1 results to quality control during production, proved the conservation of the pharmacological properties of the nebulized extract of A. pyrifolium Mart. highlighting the successful results of the analgesic activity obtained in the percentage inhibition of writhing numbers of 70.6% and 89.4% for lower and higher concentration solution, respectively, instead of dipyrone, the positive control of the test, submitted the percent inhibition of 77.65% of contortions.